The Strategic Role of Female Leadership in Arabic Language Education - Zahra, Dwi Noviatul; Marhumah, Marhumah; Maragustam, Maragustam (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
A phenomenological approach was used to examine the role of female academic leadership in managing and developing Arabic Language Education programs at higher education institutions or universities in Lampung, Indonesia. It aimed to analyze female faculty members' perceptions of their leadership roles and their contributions to Arabic Language Education. Despite an increasing number of women in academic leadership, their influence in specialized fields like Arabic Language Education remains underrepresented. Data were collected through in-depth interviews with female faculty leaders at four universities, participatory observations within academic departments, and document analysis, including institutional policies, curricula, and meeting records. The interviews explored leadership roles, challenges, strategies, and their impact on educational development, while observations captured decision-making processes and interactions. This article revealed the distinctive leadership strategies of female faculty members, highlighting their ability to shape inclusive, gender-equitable educational policies and practices. Their leadership is characterized by decisiveness and strong commitment to student success, despite facing professional-personal challenges and limited institutional support. It was implied that institutions should provide more targeted support for female leaders through leadership training, policies promoting work-life balance, and the removal of structural gender barriers, which would enhance their leadership potential and improve Arabic Language Education. The significance of this research lied in its contribution to understanding how female leadership could influence academic development in male-dominated fields and how supportive policies could create a more inclusive academic environment. Future research should explore the long-term impacts of female leadership in various academic fields and regions.